Penerapan Metode Mind Mapping dalam Peningkatan Prestasi Belajar IPA Siswa Kelas 5 SDIT Cordova Samarinda - Desi Hermawati (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
The purpose of the research is to improve students' science learning achievement of fifth grade student in SDIT Cordova Samarinda. This research is a Classroom Action Research which conducted in the fifth grade elementary school of SDIT Cordova Samarinda’s students as the subject. This action research conducted in three cycles which executed on September until October 2012. The data was collected through observations, interviews, final scores and documentation. Data analyzing with qualitative data analysis model by Miles and Huberman. The steps of data analysis are data reduction, data display and conclusion drawing/ verification. In addition also performed a quantitative data analysis using Paired Sample t-Test tested the significance level of improvement of learning achievement before and after using Mind Mapping method. The results of this research show the application of Mind Mapping method can improve the learning process and learning achievement. Furthermore there is a significant  improvement of students achievement. However, there are some students who don’t like Mind Mapping method, so that we suggest teachers should combine the various methods and techniques to maximize the learning process and learning outcomes.